Article RETRACTED due to manipulation by the authors The effect of bow training on the endurance of the arm muscles of the beginner archery - Kukuh Wahyudin Pratama (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study aims to determine the effect of Bow Training exercises on the muscular endurance of beginner archery athletes in the Jambi City Kobar Club. The research carried out is an experimental study, which is conducted to find out presence or absence of increase from something imposed on the sample. This experimental study is carried out by the 10 people of beginner archery athlete in Kobar Club, with the details of the Pre-test, the test before doing the Bow Training and the Post-test, after doing the Bow Training. The overall results of the Pre-test points for endurance of the arm muscles by 113 points with an average endurance of the arm muscles of 11.30 points. While the overall results of points in the Post-test of endurance of the arm muscles by 151 points with an average endurance of the arm muscles of 15.10 points. Based on the results of this study it can be concluded that a person who is given Bow Training exercises will have arm muscle endurance exercises 3.8 points better than someone who is not given training. The results show that the hypothesis proposed is the existence of a significant effect of bow training exercises on increasing endurance of the arm muscles received with a 95% confidence level that can be seen from the results of the t-test that is t = 13.07684 greater than t table = 1.8331. So it can be conclude that the Bow Training exercises can increase endurance of the arm muscles by 11.237%. This means that there is a significant effect of Bow Training exercises on the endurance of the beginner's arm archery athletes in the Jambi City Kobar club.